Molecular Biotechnology : Principles and practices - Channarayappa (University press, 2006)
Covers a range of molecular techniques in biotechnology. Each technique in this work is described conceptually, followed by a detailed experimental account of the steps involved. It also serves as reference to the reader who is venturing into the field of biotechnology for the first time.